Implementation of Credit Agreement with Civil Servant Appointment Decree Guarantee - Manan, Najwa Septianingsih; Tanudjaja, Tanudjaja (Faculty of Law, University of Mataram, 2025)
This study analyzes the legal review of credit agreements secured by the Appointment Decree of Civil Servants as collateral. The research method used is qualitative juridical normative with a statutory approach. The findings indicate that banks need to assess the repayment capacity of potential borrowers according to their ability, mainly when the SK PNS is used as loan collateral. The certainty of the civil servant's basic salary and the provision of a Salary Deduction Power of Attorney are key factors that assure the bank of the civil servant's ability to repay the credit debt.